First note the key definitions:
Def InvFuns(A;B;f;g) == ( x:A. g(f(x)) = x) & (
y:B. f(g(y)) = y)
Def Bij(A; B; f) == Inj(A; B; f) & Surj(A; B; f)
It turns out that each conjunct of the conclusion will follow from a conjunct of the premise, namely,
( , andx:A. g(f(x)) = x)
Inj(A; B; f)
( .y:B. f(g(y)) = y)
Surj(A; B; f)
To show
f(a1) = f(a2) , which is so sincea1 = a2
f(a1) = f(a2) , andg(f(a1)) = g(f(a2))
g cancelsf by assumption,so,
a1 = a2 .
To show
b:B.
a:A. f(a) = b
which is witnessed by
g(b) thus:
, which follows from our assumption. b:B. f(g(b)) = b
QED
About:
![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() |